Biased Supervision - Josse Delfgaauw; Michiel Souverijn (Tinbergen Institute, 2014)
When verifiable performance measures are imperfect, organizations often resort to subjective performance pay. This may give supervisors the power to direct employees towards tasks that mainly benefit the supervisor rather than the organization. We cast a principal-supervisor-agent model in a multitask setting, where the supervisor has an intrinsic preference towards specific tasks. We show that subjective performance pay based on evaluation by a biased supervisor has the same distorting effect on the agent's effort allocation as incentive pay based on an incongruent performance measure. If the principal can combine incongruent performance measures with biased supervision, the distortion in the agent's efforts is mitigated, but cannot always be eliminated. We apply our results to the choice between specialist and generalist middle managers, where a trade-off between expertise and bias may arise.
Keywords: J24; M12; M52; 330; subjective performance evaluation; middle managers; incentives; multitasking